(untitled) - Lynch, Richard (San Francisco, Calif., 2005)
In this thorough update of his award-winning best-seller, Richard Lynch supplies those tools, plus the in-depth background and detailed instruction you need to apply them effectively. In no time, you'll be using Photoshop Elements to get results you never thought possible.
Keywords: Photography,Computer graphics,Nhiếp ảnh,Đồ họa máy tính.; Digital techniques,Kỹ thuật số